2005
DOI: 10.1103/physrevd.71.043520
|View full text |Cite
|
Sign up to set email alerts
|

Wormholes supported by a phantom energy

Abstract: We extend the notion of phantom energy-which is generally accepted for homogeneously distributed matter with w < −1 in the universe-on inhomogeneous spherically symmetric spacetime configurations. A spherically symmetric distribution of phantom energy is shown to be able to support the existence of static wormholes. We find an exact solution describing a static spherically symmetric wormhole with phantom energy and show that a spatial distribution of the phantom energy is mainly restricted by the vicinity of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
433
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 432 publications
(438 citation statements)
references
References 22 publications
5
433
0
Order By: Relevance
“…It is also interesting to note that in the limit a → ∞, the volume integral tends to a finite value, i.e., I V = −6r 0 /5. This proves that as in the specific case of phantom [8] and Chaplygin [18] wormholes, one may theoretically construct a wormhole with arbitrarily small amounts of a VDW quintessence fluid. As emphasized in Ref.…”
Section: Vdw Quintessence Traversable Wormholesmentioning
confidence: 89%
See 2 more Smart Citations
“…It is also interesting to note that in the limit a → ∞, the volume integral tends to a finite value, i.e., I V = −6r 0 /5. This proves that as in the specific case of phantom [8] and Chaplygin [18] wormholes, one may theoretically construct a wormhole with arbitrarily small amounts of a VDW quintessence fluid. As emphasized in Ref.…”
Section: Vdw Quintessence Traversable Wormholesmentioning
confidence: 89%
“…Therefore, the pressure in the VDW equation of state may be regarded a radial pressure, and the transverse pressure is determined through the Einstein field equations. The justification of this approach may be considered as an extension of the construction of inhomogeneous wormhole spacetimes supported by phantom energy [8]. The latter construction was motivated by the analysis carried out in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] explicitly demonstrated that the phantom energy can support the existence of static wormholes. Hence, our observation that the holographic dark energies, when accreting on wormhole, leading to an increase in the wormhole mass in the phantom phase of the universe is in agreement with [61]. Also, the study is in agreement with [18], who showed that accretion of two types of Chaplygin gas onto Morris-Thorne Wormhole lead to increase in wormhole mass in the phantom phase of the universe.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [61] explicitly demonstrated that the phantom energy can support the existence of static wormholes. Hence, our observation that the holographic dark energies, when accreting on wormhole, leading to an increase in the wormhole mass in the phantom phase of the universe is in agreement with [61].…”
Section: Discussionmentioning
confidence: 99%